Analysis of Buyer Trust in Web E-Commerce Shop and Travel - Eri Mardiani; Nur Rahmansyah; Satriawan Desmana; Ahmad Rifqi (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
The development of information technology is increasing rapidly until now the latest technologies are being developed so that the role of technology can also improve the regional economy. Economic growth and technological developments in the business world have developed very rapidly, marked by the emergence of companies that are trying to create products and services to meet consumer needs. Business development illustrates that people's welfare is increasing, thus causing an increase in people's purchasing power. This study aims to develop a research model that uses Kim's approach model by representing based on Trust, Benefit, Risk, Intention and Purchasing with this model so that factors can be identified. anything that influences public trust to conduct online transactions (E-commerce), especially on web shops and travel.